Analisis Keberhasilan E-Learning Universitas Dalam Perspektif Sistem Informasi - Agus Prasetyo Utomo -; Andiyan Bagas Alfiandika (STEKOM PRESS, 2022)
Stikubank University (Unisbank) Semarang has implemented a web-based learning system known as a smart campus in which there is an integrated smart campus e-learning model. E-learning applied by Unisbank management is an online learning medium by utilizing information technology to make it easy for all students and lecturers to use in the teaching and learning process. This study aims to analyze the success of university e-learning based on the adaptation of the Delone and McLean information system success model. Primary data and secondary data were used in this study, a questionnaire instrument was used to obtain primary data. Furthermore, the data is processed quantitatively using the Smart PLS 3.0 software. The results of the data test were then analyzed descriptively to provide a narrative description of the research results. The results of research data processing showed that (1) Student assessment of system quality in the e-learning system had no significant effect on intention to use with a p-value of 0.729; (2) Student assessment of system quality in the e-learning system has a significant effect on user satisfaction with a p-value of 0.002; (3) Student assessment of information quality in the e-learning system has a significant effect on intention to use with a p-value of 0.025; (4) Student assessment of information quality in the e-learning system will have a significant effect on user satisfaction with a p-value of 0.000; (5) Student assessment of service quality in the e-learning system has no significant effect on intention to use with a p-value of 0.166; (6) Student assessment of service quality in the e-learning system will have a significant effect on user satisfaction with a p-value of 0.000; (7) User satisfaction related to the e-learning system has a significant effect on intention to use with a p-value of 0.000; (8) Intention to use e-learning system has a significant effect on net benefits p-value 0.004; (9) User satisfaction in the e-learning system has a significant effect on net benefits with a p-value of 0.000. Keywords: PLS, SEM, SmartPLS 3.0, E-Learning, Information Systems success, Delone & McLean Model.